Competitividad en las empresas del sector construcción en el cantón Latacunga - Gallegos Gallardo, Dayanara Miroslaba (2022)
The present work entitled competitiveness in companies in construction sector on Latacunga canton, had the objective to explaining since various perspectives and approaches the competitiveness in the construction sector, calculating cantonal competitiveness index for Latacunga considering economic- Business, Infrastructure, socio-demographic, Institutional, environmental, and determining the competitiveness index of construction sector in Latacunga Canton. The applied methodology was quantitative, descriptive and bibliographical. Data collection technique used was survey to 142 companies, the results indicate that it obtained Cantonal Competitiveness indices with 0.7172 and Business with 0.4577, the values of these indices were averaged as a result, a competitiveness index was achieved from construction sector of Latacunga canton of 0.59 which means being located at II Stage of Competitiveness (Acceptable- Regular level of competitiveness).